A comparative study to evaluate diagnostic agreement of IMNCI algorithm in young infants - Bansal, Rishi; Kshitij Sharma, Ram; Nayak, Madhu; Firoz, Shehraz (Pediatric Review: International Journal of Pediatric Research, 2019)
Background: Under-five and infant mortality constitutes a major health problem in India. To combat this high mortality, IMCI strategy aiming at holistic and integrated approach to child health and development was developed by WHO. Methods: This study is a comparative study conducted at Emergency and Outpatient Department of Pediatrics FHMC Tundla and SNMC Agra. Total of 200 young infants(0-2months) were taken. Detailed history and examination was done for all enrolled young infants according to IMNCI and for enrolled infants diagnosis and treatment was made in the Pediatric Department and was considered as Gold Standard. Results: Out of total 200 young infants, 117 were 0-7 days of age and rest 83 were 7- 59 days of age. Of these 109 infants were admitted, and 91 infants were sent home after initial management. There was no mismatch in diagnosis of 48% infants, while partial mismatch in 38.5% infants, over diagnosis in 10.5% and under diagnosis was present in 3% infants of 0-2 months of age. Conclusion: This study had good diagnostic agreement and only 3%of infants were underdiagnosed.